Designing a Methodology for Semantic Type Tagging of Argument Positions - Francesca Della Moretta; Anna Feltracco; Elisabetta Jezek; Bernardo Magnini (IJCoL)
A verb argument position can be described by the semantic type that characterizes the words filling that position. We investigate a number of linguistic issues underlying the tagging of an Italian corpus with the semantic types provided by the T-PAS (Typed Predicate-Argument Structure) resource. Our main interest is to evaluate whether our annotation methodology can be employed effectively for the extension of the annotation of the corpus associated with the resource. In order to achieve this goal we compare quantitative data about the tagging and qualitative data derived from the Inter-Annotator Agreement.